Factors associated with the spatial accessibility of healthcare services measured by the floating catchment area (FCA)-based method: A scoping review - Ab Hamid, Jabrullah; Juni, Muhamad Hanafiah; Abdul Manaf, Rosliza; Syed Ismail, Sharifah Norkhadijah; Lim, Poh Ying (Malaysian Medical Association, 2023)
Introduction: The floating catchment area (FCA) method has emerged as the most comprehensive and accurate method for quantifying the spatial accessibility of health care services. There were variants of the FCA-based method that was continuously improvised by the researchers to suit specific local contexts and the different nature of healthcare service delivery. This scoping review identifies factors associated with the spatial accessibility of healthcare services that were specifically measured using the FCAbased method